2015
DOI: 10.5902/2236130819948
|View full text |Cite
|
Sign up to set email alerts
|

O programa Rio Rural no estado do Rio de Janeiro: a experiência na microbacia canal Jurumirim, município de Macaé

Abstract: Do ponto de vista físico, microbacia hidrográfica é uma unidade geográfica delimitada por uma rede de drenagem (córregos) que deságua em um rio principal. O Rio Rural é um programa de financiamento que usa a metodologia participativa para sua implementação. No início do processo os membros da microbacia se reúnem em grupos de interesse elegendo seus representantes para comporem o chamado Comitê Gestor da Microbacia, o COGEM, que acompanhará o técnico executor em todas as fases do programa, até o controle. Vári… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Regarding the protection of the site with fences, it was found that out of the 21 shallow wells evaluated, four did not have any type of fences in the surroundings, twelve had fences with access, and five were fenced without access. The presence of fences is of great importance (Malaquias;Cândido, 2013), as it contributes positively to the water sources, as they prevent the access of animals, thus avoiding the trampling of animals (change in the color and turbidity of the water), defecation (presence of fecal coliforms and change in water odor) (Athaydes;Parolin;Crispim, 2022) and soil degradation (Ferraz;Lago;Bagos, 2017), thus allowing the regeneration of nearby plant species (Rangel;Moreira, 2006). Gomes, Melo and Vale (2005) report that when there is no protection system, the probability of human interference on water becomes greater.…”
Section: Conditions Of Land Use and Ocupationmentioning
confidence: 99%
“…Regarding the protection of the site with fences, it was found that out of the 21 shallow wells evaluated, four did not have any type of fences in the surroundings, twelve had fences with access, and five were fenced without access. The presence of fences is of great importance (Malaquias;Cândido, 2013), as it contributes positively to the water sources, as they prevent the access of animals, thus avoiding the trampling of animals (change in the color and turbidity of the water), defecation (presence of fecal coliforms and change in water odor) (Athaydes;Parolin;Crispim, 2022) and soil degradation (Ferraz;Lago;Bagos, 2017), thus allowing the regeneration of nearby plant species (Rangel;Moreira, 2006). Gomes, Melo and Vale (2005) report that when there is no protection system, the probability of human interference on water becomes greater.…”
Section: Conditions Of Land Use and Ocupationmentioning
confidence: 99%